Analysis of Factors Hindering the Implementation of Electronic Medical Records at Pertamina Rantau Hospital - Fita Rusdian Ikawati; Syawalina; Harahap, Riska Mutiara Nova (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Indonesian government recognizes that with the rapid advancement of technology, conventional medical records are no longer relevant in today's conditions. Digitalizing healthcare services is essential, which means that patient medical records must be stored electronically. Based on interviews and observations conducted by researchers, it was found that the use of electronic medical records at Pertamina Rantau Hospital has not been fully optimized. Therefore, the purpose of this research is to identify the factors that hinder the implementation of electronic medical records at Pertamina Rantau Hospital. This study is qualitative, using observation and interview methods. It is undeniable that there will be many obstacles or problems encountered when implementing electronic medical records. One of the most influential factors is the four elements of medical record management: man, material, machine, and method. To achieve digital transformation of the healthcare system in Indonesia, adequate facilities are needed. Hospital policies are also one of the biggest keys to the implementation of electronic medical records. Therefore, hospitals are expected to establish firm policies regarding the implementation of electronic medical records at Pertamina Rantau Hospital